If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(1 + 7x) + -6(-7 + -1x) = 6 (1 * -1 + 7x * -1) + -6(-7 + -1x) = 6 (-1 + -7x) + -6(-7 + -1x) = 6 -1 + -7x + (-7 * -6 + -1x * -6) = 6 -1 + -7x + (42 + 6x) = 6 Reorder the terms: -1 + 42 + -7x + 6x = 6 Combine like terms: -1 + 42 = 41 41 + -7x + 6x = 6 Combine like terms: -7x + 6x = -1x 41 + -1x = 6 Solving 41 + -1x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-41' to each side of the equation. 41 + -41 + -1x = 6 + -41 Combine like terms: 41 + -41 = 0 0 + -1x = 6 + -41 -1x = 6 + -41 Combine like terms: 6 + -41 = -35 -1x = -35 Divide each side by '-1'. x = 35 Simplifying x = 35
| 7n-8+2+7n=0 | | -4(2+m)=2(m-7) | | 60y-108+12= | | Q+2=q+16 | | 12=1/3z+7 | | -4y^3-8xy^4=4y^3(1+2xy) | | 4y=5x+4 | | X-32=4(12-y) | | -6+4s=-2 | | 2u+4=16 | | 2(7x+3)=20 | | -2x+8x-7=6(x-4)-3 | | 0=3x^2-x-120 | | -6v+3v-9=-3 | | 4z+6=2z+6 | | -9=7(7v+8)+4(5v+1) | | 3(a-1)-5=34 | | 0.25(8z-4)=1z+8-2z | | 8-9+4b-5f= | | 4[5x-(2x-7)]=2(4x-5) | | 4k-13=11 | | 54=2x-9+4x | | 3(x+4)=2+3x | | 7-3r=r-8-4r | | 12-7(x-4)+x=-12 | | 2.5z=46 | | -60+20x=20x+-20x | | 0.7x+0.15x=62 | | 3(5p-9)-4(p+7)= | | -7(1+n)=-1+5n | | 35*3x+4=70 | | -7(x+4)-42=8-29 |